Low haemoglobin concentration in Tibetan males is associated with greater high‐altitude exercise capacity. (25th June 2015) - Simonson, T. S.; Wei, G.; Wagner, H. E.; Wuren, T.; Qin, G.; Yan, M.; Wagner, P. D.; Ge, R. L.
Abstract : Key points: We hypothesized that sea‐level range haemoglobin concentration ([Hb]) at altitude, previously linked with adaptive genetic factors in Tibetans, would be associated with greater exercise capacity, explained by changes in steps of the oxygen transport system in this population. In 21 Tibetan and 9 Han Chinese males resident at 4200–4300 m, we measured [Hb], ventilation, volumes of O2 and CO2 utilized at peak exercise ( V ̇ O 2 and V ̇ C O 2 ), heart rate, cardiac output and arterial blood gas variables at peak exercise on a cycle ergometer and determined oxygen (O2 ) diffusion capacity in lung and muscle. Tibetans with low [Hb] exhibit greater peak V ̇ O 2 kg –1, which was explained mostly by variation in cardiac output, ventilation and O2 diffusional conductances in muscle. These results suggest that polycythaemia may be an excessive response to low P O 2 at altitude. Abstract: Tibetans living at high altitude have adapted genetically such that many display a low erythropoietic response, resulting in near sea‐level haemoglobin (Hb) concentration. We hypothesized that absence of the erythropoietic response would be associated with greater exercise capacity compared to those with high [Hb] as a result of beneficial changes in oxygen transport. We measured, in 21 Tibetan males with [Hb] ranging from 15.2 g dl −1 to 22.9 g dl −1 (9.4 mmol l −1 to 14.2 mmol l −1 ), [Hb], ventilation, volumes of O2 and CO2 utilized at peak exercise ( V ̇ O 2 and V ̇ C O 2 ), heart rate, cardiac output and arterial blood gas variables at peak exercise on a cycle ergometer at ∼4200 m. Lung and muscle O2 diffusional conductances were computed from these measurements. [Hb] was related (negatively) to V ̇ O 2 kg –1 ( r = −0.45, P < 0.05), cardiac output kg –1 (QT kg –1, r = −0.54, P < 0.02), and O2 diffusion capacity in muscle (DM kg –1, r = −0.44, P <0.05), but was unrelated to ventilation, arterial partial pressure of O2 ( P a O 2 ) or pulmonary diffusing capacity. Using multiple linear regression, variance in peak V ̇ O 2 kg –1 was primarily attributed to QT, DM, and P C O 2 ( R 2 = 0.88). However, variance in pulmonary gas exchange played essentially no role in determining peak V ̇ O 2 . These results (1) show higher exercise capacity in Tibetans without the erythropoietic response, supported mostly by cardiac and muscle O2 transport capacity and ventilation rather than pulmonary adaptations, and (2) support the emerging hypothesis that the polycythaemia of altitude, normally a beneficial response to low cellular P O 2, may become maladaptive if excessively elevated under chronic hypoxia. The cause and effect relationships among [Hb], QT, DM, and P C O 2 remain to be elucidated.